2007
DOI: 10.1016/j.proci.2006.07.202
|View full text |Cite
|
Sign up to set email alerts
|

Studies of radiation absorption on flame speed and flammability limit of CO2 diluted methane flames at elevated pressures

Abstract: The effects of spectral radiation absorption on the flame speed at normal and elevated pressures were experimentally and numerically investigated using the CO 2 diluted outwardly propagating CH 4 -O 2 -He flames. Experimentally, the laminar burning velocities of CH 4 -O 2 -He-CO 2 mixtures at both normal and elevated pressures (up to 5 atm) were measured by using a pressure-release type spherical bomb. The results showed that radiation absorption with CO 2 addition increases the flame speed and extends the fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(52 citation statements)
references
References 38 publications
2
46
1
1
Order By: Relevance
“…Radiation emission/absorption brakes this balance and is able to modify both the flammability limits and the flame propagation speeds, see e.g. [16]. This is especially important in microgravity [17].…”
Section: Radiation Preheatingmentioning
confidence: 99%
“…Radiation emission/absorption brakes this balance and is able to modify both the flammability limits and the flame propagation speeds, see e.g. [16]. This is especially important in microgravity [17].…”
Section: Radiation Preheatingmentioning
confidence: 99%
“…Ju and co-workers showed that radiation absorption and emission are important in flames with high CO 2 dilution, since CO 2 is a strong absorber [58][59]. Chen et al [58] indicated that spectral dependent radiation absorption must be included for any quantitative predictions of flame speed with CO 2 dilution.…”
Section: Effect Of Co 2 Dilution On the Pressure And Flame Temperaturmentioning
confidence: 99%
“…Chen et al [58] indicated that spectral dependent radiation absorption must be included for any quantitative predictions of flame speed with CO 2 dilution. The effect of radiation is not considered in detail here, and we refer the reader to Refs.…”
Section: Effect Of Co 2 Dilution On the Pressure And Flame Temperaturmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a little attempt is made on the issue of flame propagation in the tube/channel with the addition of local heating. It is reported by Ju et al [17] and Chen et al [18] that the self-absorption of radiation emitted from the flame has significant effect on burning velocity and flammability limits. Obviously, this selfabsorption of emitted radiation from the flame is mild while the absorption of an external radiation is strong in nature.…”
Section: Introductionmentioning
confidence: 99%